Unbearing burden of the refugee crisis on developing countries: Is the global compact on refugees the solution? - Rimber, Kimberly Wangeci (University of Cape Town, 2021)
This research analyses the Global Compact on Refugees("GCR"), adopted in 2018 by the United Nations General Assembly. It aims to discuss whether the document, a non-legal document offers durable solutions to developing countries who host more than 80% of the world´s refugees and asylum seekers population. The paper does this by outlining the key components of the GCR, doing a comparative study of Kenya and Jordan, and looking at what impact the GCR might have had on the programs already running in Kenya and Jordan. The two countries were chosen as they were part of the Comprehensive Refugee Response Framework countries, which greatly influenced the development of the GCR. The paper comes to the conclusion that the GCR has great potential in dealing with the Refugee crisis in the world, but this is hinged on the political will of the developed countries and international cooperation. The research underlines topical issues in international refugee protection such as "accidents of geography" that leads to most refugees seeking refuge in neighbouring countries, which more often are not are developing countries. The research paper further gives the strengths of the GCR, critiques it and gives recommendations based on the comparative studies.